2007
DOI: 10.1016/j.neuroscience.2006.08.073
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amphetamine analogs on cleaved microtubule-associated protein-tau formation in the rat brain

Abstract: The present study quantified the cleaved form of the microtubule associated protein tau (cleaved MAP-tau, C-tau), a previously demonstrated marker of CNS toxicity, following the administration of monoamine-depleting regimens of the psychostimulant drugs amphetamine (AMPH), methamphetamine (METH), ±3,4-methylenedioxymethamphetamine (MDMA), or paramethoxyamphetamine (PMA) in an attempt to further characterize psychostimulant-induced toxicity. A dopamine (DA)-depleting regimen of AMPH produced an increase in C-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
(70 reference statements)
0
13
1
Order By: Relevance
“…In contrast to previously published observations using the acute toxic dosing model (i.e., four injections of METH every 2 h; Daberkow et al, 2005;Eyerman and Yamamoto, 2005;Friedman et al, 1998;Ricaurte et al 1982;Straiko et al, 2007;Wallace et al, 2001), METH administration to rats not exposed to CUS did not produce depletions in 5-HT tissue content (Fig. 3B).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previously published observations using the acute toxic dosing model (i.e., four injections of METH every 2 h; Daberkow et al, 2005;Eyerman and Yamamoto, 2005;Friedman et al, 1998;Ricaurte et al 1982;Straiko et al, 2007;Wallace et al, 2001), METH administration to rats not exposed to CUS did not produce depletions in 5-HT tissue content (Fig. 3B).…”
Section: Discussioncontrasting
confidence: 99%
“…However, in general, data referring to glial activation after neurotoxic regimens of MDMA are not consistent. A few studies report an increase in GFAP expression in the context of MDMA-induced neurotoxicity [286,292,293], whereas others do not [280,294,295]. Also, with the established 5-HT neurotoxicant, 5,7-DHT, data from different studies are also not consistent, with some studies revealing increased GFAP expression after neurotoxic regimens [280,296,297], whereas others do not [295,298].…”
Section: Mdma-induced Neurotoxicity To the Rat-biochemical And Histolmentioning
confidence: 99%
“…A few studies report an increase in GFAP expression in the context of MDMA-induced neurotoxicity [286,292,293], whereas others do not [280,294,295]. Also, with the established 5-HT neurotoxicant, 5,7-DHT, data from different studies are also not consistent, with some studies revealing increased GFAP expression after neurotoxic regimens [280,296,297], whereas others do not [295,298]. It has been suggested that a lack of GFAP expression increase may be due to an insufficiently strong signal and that the use of this parameter for detecting degeneration of serotonergic termi- Decreased survival of neuronal precursors incorporated in the dentate gyrus of the HIP 5 mg/kg, i.p., eight doses, 1 day 14 [285] The table summarizes the findings on markers of neuronal degeneration in the rat brain after MDMA treatment.…”
Section: Mdma-induced Neurotoxicity To the Rat-biochemical And Histolmentioning
confidence: 99%
“…However, when considering this line of reasoning, it is important to recognize that established 5-HT neurotoxins (e.g. 5, 7-DHT) also fail to consistently induce a glial reaction in brain regions distant from the site of intracerebral toxin injection (see Hardin et al, 1994;Frankfurt and Azmitia, 1984;Rowland et al, 1993;Bendotti et al, 1994;Straiko et al, 2007). Thus, in our view, rather than casting doubt on the neurotoxic potential of MDMA and other substituted amphetamines (e.g.…”
Section: Serotonin Neurotoxicitymentioning
confidence: 99%